The Marital Sexual Experiences of South African Muslim Wives of Indian Descent: Interpretative Phenomenological Analysis - Maryam Khan; Sumayya Ebrahim (Journal for the Study of Religion, 2024)
This article2 explores the sexuality of South African Muslim Indian wives in monogamous marriages, analyzing the effect of religious teachings and cultural norms on sexual experiences using hermeneutic phenomenology. The abrupt shift from religious norms that promote chastity to the expectation of sexual activity upon marriage, together with variations in desire and sexual preferences remain relatively underexplored within Muslim marriages. Under analysis is the dynamic between intimacy, desire, and shame. Drawing on empirical research, results highlight emotional and psychological challenges faced by Muslim women during marital sexual initiation due to their interpretations of religious teachings and limited sex education. Muslim wives experience that their sexual desire discrepancies negatively impact their mental health and self-esteem. There is the invocation of gendered sexual conceptions perpetuated by cultural conditioning which is also negotiated and subverted. Despite challenges, a transformative potential in marital relationships is indicated through agentival capacity, understanding, communication, and mutual sexual satisfaction.